The Effectiveness of the Combination of Hypnotherapy and Physical Activity in Reducing Anxiety Disorders in Elementary School Students - Binangun, Aqso; Nur Asniati Djaali; Titi Indriyati (LPPM Universitas Mohammad Husni Thamrin, 2026)
Anxiety disorders in elementary school-aged children in urban settings show an increasing trend that requires contextual intervention. This study aims to analyze the effectiveness of a combination of hypnotherapy and physical activity compared to a single physical activity intervention in reducing anxiety levels in phase C students at SDN Pondok Kelapa 05 Pagi. Using a quasi-experimental design, 64 students were divided into an intervention group (n=31) and a control group (n=33). The research instrument used the Spence Children's Anxiety Scale (SCAS) questionnaire. The results of the bivariate analysis showed that the intervention group experienced a more significant decrease in anxiety scores (6.97 points) compared to the control group (2.70 points) with a p value of 0.01. However, the multivariate analysis showed that gender was the most dominant factor, where male students were 3.2 times more likely to experience a decrease in anxiety (p=0.043). This study concludes that the combination intervention provides promising added value for managing complex anxiety in schools. This research is very important to fill the literature gap regarding combination interventions in non-clinical elementary school settings. Practically, this study offers a low-cost and applicable solution for public schools in urban settings with limited resources for mental health professionals. By testing the synergy between hypnotherapy and physical activity, this research is expected to provide an effective coping model for students facing the stress of the metropolitan environment.